Prevalence and determinants of caesarean section in a rural community of Nalgonda District, Telangana - Karna, Jahnavi; Malhotra, Varun M. (International Journal Of Community Medicine And Public Health, 2017)
Background: The rapid increase of caesarean section rates globally is a public health concern because rates higher than those recommended by WHO do not contribute to improved maternal health and pregnancy outcome. This study aims to estimate the prevalence of caesarean section, establish relationship of relevant variables with caesarean section, and identify temporal trends of c-sec rates in rural populace of Nalgonda. Methods: A community-based cross-sectional analytic study was undertaken in rural field practice area of Kamineni Institute of Medical Sciences. Data were collected on structured questionnaire from selected and consenting women in reproductive age group who had delivered since 01 January 2000. Results: Our study included 224 study subjects who have undergone 389 deliveries. Of these 54% were by caesarean section and 46% were normal deliveries. Age of mother, type of family, educational status of mother, height of mother and place of delivery were identified as relevant variables. Their association with C-sec rates and time trend of c-sec rates are presented. Conclusions: Multi centre, large-sampled and ‘in depth’ studies are needed to analyze the problem of very high caesarean section rates. These would provide qualitative and quantitative data to plan strategies to reduce the prevalence of a surgical procedure that if carried out on ‘non-medical grounds’ has the potential to cause obstetrical and neonatal complications, and significant economical and health-planning implications.